An approach to assess stress in response to drive hunts using cortisol levels of wild boar (Sus scrofa) - Justine Güldenpfennig (Nature Portfolio, 2021)
Abstract Hunting can easily be linked to stress in wildlife. Drive hunts performed two to three times in one area during the respective hunting period, are thought to decrease the pressure hunting places on wildlife. Nevertheless, the expression of cortisol—one of the main mammalian stress hormones—is considered to have negative impacts on animals’ well-being if expressed excessively, which may occur during some (especially repeated) hunting events. We explored the effect of drive hunts on cortisol levels in wild boar in Lower Saxony, Germany, compared these cortisol levels to reference values given by a similar study, and investigated the effect of age, sex, and pregnancy. Blood collected from wild boar shot on drive hunts was analysed using a radioimmunoassay. As expected, we observed elevated cortisol levels in all samples, however, we still found significant differences between age groups and sexes, as well as an influence of pregnancy on cortisol levels. The effect of drive hunts on cortisol levels appears to be weaker than predicted, while the effects of other variables, such as sex, are distinct. Only half of the evaluated samples showed explicitly increased cortisol levels and no significant differences were found between sampling months and locations. Group living animals and pregnant females showed significantly higher cortisol levels. The impact of hunting is measurable but is masked by natural effects such as pregnancy. Thus, we need more information on stress levels in game species.